Pemberian Imunisasi Hb 0 Pada Bayi Baru Lahir Usia 2 Hari - Arantya, Nina Qurain; Siti Maryam; Dita Retno Pratiwi (YAYASAN HAMJAH DIHA bekerjasama dengan PENA INSTITUTE, 2025)
Hepatitis B is an infectious disease and generally infects the liver caused by the hepatitis B virus (HBV), which causes one way to prevent transmission from occurring is to take precautions, namely by providing hepatitis B immunization to newborn babies. Nenonates are babies born vaginally without any instruments (Jamil et al., 2020). The prevalence of Hepatitis B in Indonesia is caused by delays in immunization. There are still many cases of hepatitis B transmission from mothers giving birth to babies, which is the main cause. The high level of vertical transmission from mother to baby is caused by delays in administering Hepatitis B vaccination to their babies (Sifa, 2020). Babies infected with the Hepatitis B virus are at risk of developing chronic liver disease. Transmission of this virus can be prevented by immediate vaccine immunization within a maximum of 12 hours (Permanasari, 2020). The aim of this community service activity is to increase the knowledge of mothers and families about providing hepatitis B immunization to newborns and preventing transmission of hepatitis disease. The method used is counseling and question and answer. This activity will take place on October 24 2024 at Mr. T, counseling is carried out for approximately 1 hour from 10:00 WITA to 11:00 WIT, followed by a physical examination of newborns and administration of Hepatitis B0 immunization. The tool used to provide education about hepatitis B0 immunization is leaflets. The results of this activity show that the majority of respondents have a positive attitude due to several factors, one of which is knowledge so that it can influence a person's attitude. Sufficient sources of information and a desire to find out so that respondents can have a positive attitude. According to the author, if the respondent's education level is high, it can make it easier for the respondent to receive various information and have an open mind. Good knowledge can reflect a positive attitude. However, even though most respondents had less knowledge, respondents supported it by being positive.